Influence of bariatric surgery on quality of life, body image, and general self-efficacy within 6 and 24 months: a prospective cohort study - Nickel, Felix; Schmidt, Lukas; Bruckner, Thomas; Büchler, Markus W.; Müller, Beat P.; Fischer, Lars (Surgery for obesity and related diseases, 2017)
To evaluate QOL, body image, and general self-efficacy (GSE) in patients with morbid obesity undergoing bariatric surgery within clinical parameters.